Visionary Leadership of Madrasah Heads in Improving Brand Awareness and the Competitiveness of the Institution in Madrasah Tsanawiyah - Fauzi, Muhammad; Abun, Ahmad Rifa'i; Mujiyatun, Mujiyatun (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
The visionary leadership of madrasah heads is an important factor in building public awareness and competitiveness of Islamic educational institutions in the midst of competition between educational institutions. This study aims to analyze the visionary leadership of madrasah heads in increasing brand awareness and institutional competitiveness in MTs Al Hidayah Marga Agung, MTs Raudlatul Jannah, and MTs Mathla'ul Anwar Rawa Selapa, South Lampung Regency. This study uses a qualitative approach with a multi-site case study type. Research data was obtained through interviews, observations, and documentation with data sources of madrasah heads, teachers, education staff, students, parents, madrasah committees, and institutional documents. Data analysis is carried out through data reduction, data presentation, and conclusion drawn. The results of the study show that the visionary leadership of madrasah heads is realized through the formulation of a clear vision, vision communication, development of superior programs, strengthening Islamic values, improving service quality, stakeholder involvement, and managing public image and trust. These findings confirm that madrasah brand awareness is not only formed through promotion, but through the consistency of vision, program quality, madrasah culture, and positive experiences of the community. This study concludes that visionary leadership contributes to increasing the competitiveness of madrassas through the formation of a differentiating identity, strengthening reputation, and increasing public trust.